A Highly Stable Zeotype Mesoporous Zirconium Metal–Organic Framework with Ultralarge Pores. Issue 1 (10th November 2014) - Feng, Dawei; Wang, Kecheng; Su, Jie; Liu, Tian‐Fu; Park, Jihye; Wei, Zhangwen; Bosch, Mathieu; Yakovenko, Andrey; Zou, Xiaodong; Zhou, Hong‐Cai
Abstract: Through topological rationalization, a zeotype mesoporous Zr‐containing metal–organic framework (MOF), namely PCN‐777, has been designed and synthesized. PCN‐777 exhibits the largest cage size of 3.8 nm and the highest pore volume of 2.8 cm 3  g −1 among reported Zr‐MOFs. Moreover, PCN‐777 shows excellent stability in aqueous environments, which makes it an ideal candidate as a support to incorporate different functional moieties. Through facile internal surface modification, the interaction between PCN‐777 and different guests can be varied to realize efficient immobilization. Abstract : Topological rationalization is used to design a zeotype mesoporous Zr metal–organic framework. When tetrahedra (orange; see picture) with [M3 O(COO)6 ] nodes and tridentate benzene‐1, 3, 5‐tricarboxylate faces are connected in an eclipsed configuration ( D 3 h  nodes; light‐blue bar), an mtn network is formed. A 60° rotation between tetrahedra gives a staggered configuration with D 3 d ‐connected nodes (dark‐blue bar) and a β‐cristobalite network.